Implications of the arithmetic ratio of prime numbers for RSA security - Ivanov, Andrey; Stoianov, Nikolai (Zielona Góra: Uniwersytet Zielonogórski)
The most commonly used public key cryptographic algorithms are based on the difficulty in solving mathematical problems such as the integer factorization problem (IFP), the discrete logarithm problem (DLP) and the elliptic curve discrete logarithm problem (ECDLP). In practice, one of the most often used cryptographic algorithms continues to be the RSA. The security of RSA is based on IFP and DLP. To achieve good data security for RSA-protected encryption, it is important to follow strict rules related to key generation domains.
Keywords: public key cryptography; RSA encryption; public key generation rules; kleptography; fusion of number balance